INCREASED YIELD AND NUTRITIONAL VALUE OF KUMPAI GRASS (Hymenachne amplexicaulis (Rudge) Nees.) WITH ARBUSCULAR MYCORRHIZAL FUNGI AND ORGANIC FERTILIZER IN RED-YELLOW PODZOLIC SOIL - Evita Yani, Hardi Syafria, Novirman Jamarun, Mardiati Zein (International Journal of Agricultural Sciences, 2015)
Arbuscular Mycorrhizal Fungi (AMF) can help plants by improving the uptake of low P availability acidsoils. Organic fertilizers can effect the physical, chemical and biological soil. The purpose of this research is tostudy and determine the effect of AMF and organic fertilizer on increasing yield and nutritional value of kumpaigrass in red-yellow podzolic acid soils. The study design used a completely randomized 5 x 3 factorial pattern andrepeat three times. Two factors as treatment: AMF and organic fertilizer. AMF usage consisted of three levels:control (0 g/pot), AMF (10 g/pot) and AMF (20 g/pot). The organic fertilizer usage consisteds of five levels:control (0 %), manure (50 %), manure (100 %), compost (50 %) and compost (100 %). Variables measuredincluded the width of leaves, plant length, number of tillers, the yield of forage dry matter, crude protein,phosphorus, dry matter and organic matter digestibility. The results showed that the AMF and organic fertilizer hada highly significant (P<0.01) effect for all observed variables. The interaction AMF and organic fertilizers hadsignificant effect on crude protein, phosphorus and organic matter digestibility.